19-7z=3-5z+3

Simple and best practice solution for 19-7z=3-5z+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19-7z=3-5z+3 equation:


Simplifying
19 + -7z = 3 + -5z + 3

Reorder the terms:
19 + -7z = 3 + 3 + -5z

Combine like terms: 3 + 3 = 6
19 + -7z = 6 + -5z

Solving
19 + -7z = 6 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
19 + -7z + 5z = 6 + -5z + 5z

Combine like terms: -7z + 5z = -2z
19 + -2z = 6 + -5z + 5z

Combine like terms: -5z + 5z = 0
19 + -2z = 6 + 0
19 + -2z = 6

Add '-19' to each side of the equation.
19 + -19 + -2z = 6 + -19

Combine like terms: 19 + -19 = 0
0 + -2z = 6 + -19
-2z = 6 + -19

Combine like terms: 6 + -19 = -13
-2z = -13

Divide each side by '-2'.
z = 6.5

Simplifying
z = 6.5

See similar equations:

| -3x+2=8x+-1 | | 6x-5w+5x+7y+4y+3w= | | -3x+2=8x-1 | | 9+4q=1 | | 6x-6x-9x=99 | | 3*4*-2=x | | 3x^3+3x-6x=0 | | -6x-12=10+5x | | s(t)=-t^3+13t^2-40t | | 3c+4=11c | | -18=3(-a+6)+2z | | (7x^2-8)+(3x^2+1)= | | 13-4z=2z+9 | | 2x+2=-3x+6 | | 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 | | 3p=60+8p | | .2(x+100)=10 | | (-12)+6/2= | | 59-6x=3x+16 | | 20x+50b=320 | | -3x-y=17 |

Equations solver categories